Preparation method of mixed nitride composite material special-shaped antenna window
By using hybrid nitride composite materials and improved contour mold design, the problem of antenna window performance degradation at extreme temperatures was solved, achieving efficient preparation and high yield, while ensuring material uniformity and mechanical properties.
Patent Information
- Application Number
- CN202511484003.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-17
- Publication Date
- 2026-02-06
AI Technical Summary
Existing antenna window materials suffer from performance degradation at extreme temperatures, low manufacturing efficiency, low yield, and difficult demolding process, leading to easy product deformation or breakage.
By using hybrid nitride composite materials, and through improved mold design and step-by-step demolding process, combined with vapor deposition and impregnation curing technology, fiber uniformity and mechanical properties are ensured, and high-temperature resistance is improved.
The mechanical properties and high-temperature resistance of the antenna window have been improved, ensuring thermal shock resistance. The product yield is high and the overall performance is excellent.
Smart Images

Figure CN121470974A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of composite materials, and particularly relates to a preparation method of a mixed nitride composite material special-shaped antenna window. BACKGROUND
[0002] The antenna window is a key component for protecting the antenna system from external environmental influences and ensuring efficient transmission of electromagnetic waves. Its core functions include preventing damage to the antenna caused by environmental factors such as rain, sand, hail, etc., while also resisting mechanical impact and extreme temperatures. It can also reduce electromagnetic wave penetration loss, reduce refraction and radiation, and ensure the signal integrity of communication or radar systems. Existing antenna windows are mainly composed of high-temperature wave-transparent fiber reinforcements.
[0003] Common high-temperature wave-transparent fiber reinforcements include quartz fiber, alumina fiber, and nitride fiber. Quartz fiber is currently the most commercially available and highest-yielding fiber. However, research has shown that quartz fiber begins to crystallize and become brittle above 800°C, with a significant decrease in strength at 1000°C and complete loss of strength at 1200°C. This reduces the use of antenna windows in extreme temperatures.
[0004] Nitride fiber is a new generation of wave-transparent ceramic fiber with Si3N4, BN, SiBN, SiNO as the main phase. Compared with quartz fiber, it has better high-temperature mechanical properties, making nitride fiber reinforced ceramic-based wave-transparent composite materials have excellent high-temperature ablation performance, good high-temperature mechanical properties, and thermal shock resistance. It is the main development direction of future high-temperature wave-transparent materials.
[0005] Currently, large-size antenna windows use conventional flat fabric impregnation composite methods. The precursor material is difficult to penetrate to the deep inside of the fabric, resulting in low preparation efficiency, poor density, and uniformity of the composite material. In the precision machining process, it is difficult to ensure the continuity and consistency of the internal fibers of the product, which severely limits the performance of the material.
[0006] Furthermore, for antenna windows with large internal cavities and thin thickness, using ordinary profiling tool clamping impregnation composite, the fabric shape line will only fit the mold after curing, making the demolding process very difficult. During the demolding process, the lower edge of the fabric is thin, and the deformation or rupture of the fabric during the forced demolding process is extremely easy, ultimately leading to product scrap.
[0007] Therefore, it is a technical problem to be solved in the prior art to provide a nitride composite material antenna window that improves mechanical properties and high-temperature ablation resistance while ensuring thermal shock resistance, has excellent comprehensive performance, and has a high product yield. SUMMARY
[0008] The application provides a preparation method of a profiled antenna window of a mixed nitride composite material, and the profiled mold is improved and optimized from the perspective of stress decomposition in a demolding process, and the demolding process is completed in steps, so that the integrity of the material and the consistency of the fiber direction are fully ensured, the impregnation uniformity of the precursor material is improved, the mechanical properties and high-temperature resistance of the antenna window are improved, the thermal shock resistance is ensured, the product yield is high, and the comprehensive performance is excellent.
[0009] In view of the above technical problems, the application adopts the following technical solutions: A preparation method of a profiled antenna window of a mixed nitride composite material, comprising the steps of mixing, washing, pretreatment, vapor deposition, impregnation and curing, pyrolysis, rough machining and finishing, and the specific operation is as follows: 1. Mixing The boron nitride fibers and the silicon nitride fibers are mixed to form a profiled antenna window preform, the preform is in a 2.5-dimensional or 3-dimensional form, and the mass ratio of the silicon nitride fibers to the boron nitride fibers is 3:0.8-1.5.
[0010] 2. Washing The antenna window preform is placed in a mixed solution for ultrasonic oscillation for 1.8-2.3 h, the mixed solution completely immerses the antenna window preform, the ultrasonic frequency is 35-45 kHz, the ultrasonic power is 90-110 W, then the antenna window preform is left to stand for 4-6 days, after the standing is completed, the antenna window preform is transferred to an oven for drying, the oven temperature is 80-120 DEG C, the drying time is 8-24 h, and the washed antenna window preform is obtained. In the mixed solution, the volume ratio of anhydrous ethanol to acetone is 1:1-1.5.
[0011] 3. Pretreatment Silicon tetrachloride and anhydrous ethanol are mixed, stirred for 27-35 min, then Triton X-100 and trimethyl borate are added, and the pretreatment solution is obtained after uniform stirring. The washed antenna window preform is immersed in the pretreatment solution and placed in a supercritical reaction kettle, the pretreatment solution completely immerses the washed antenna window preform, then carbon dioxide is introduced, the flow rate is controlled to be 1.4-1.6 L / min, the temperature is increased to 38-42 DEG C, the pressure is 9-12 MPa, and the stirring speed is 200-230 rpm for 1.5-2.5 h, then the pressure is reduced to normal pressure at a rate of 0.2-0.4 MPa / min, after the washed antenna window preform is taken out, the washed antenna window preform is left to stand in a sealed container filled with nitrogen atmosphere for 0.8-1.2 h, then the washed antenna window preform is left to stand in an environment with a room temperature of 2.0-3.5 DEG C / min and a humidity of 78-83% for 20-24 h, after drying, the temperature is increased to 570-590 DEG C at a rate of 2.0-3.5 DEG C / min in an air atmosphere, and the temperature is kept for 1.8-2.5 h, then the temperature is increased to 880-910 DEG C at a rate of 4.0-5.0 DEG C / min, and the temperature is kept for 2.7-3.2 h, and the initial antenna window is obtained after the furnace is cooled to room temperature. The mass ratio of silicon tetrachloride, anhydrous ethanol, Triton X-100 and trimethyl borate in the pretreatment solution is 10:30-35:0.05-0.08:0.10-0.14; 4. Vapor deposition The initial antenna window is hoisted in a chemical vapor deposition furnace reaction chamber, NH3, BCl3 and H2 are introduced as reaction gases, the gas flow rates are 0.5-3 L / min, 0.1-2 L / min and 1-4 L / min respectively, the deposition temperature is 600-900 DEG C, and the deposition time is 5-8 h, so that the interface-containing antenna window preform is obtained.
[0012] 5. Impregnation and curing The clamped antenna window is transferred to a vacuum mold, vacuumized to-0.08 to-0.1 MPa, and kept for 1-2 h, and the silicon-boron-nitrogen precursor is siphoned, so that the silicon-boron-nitrogen precursor completely immerses the clamped antenna window, and the antenna window is immersed for 2-4 h, and then transferred to a high-pressure reaction kettle, the pressure is controlled to be 5-8 MPa, and the antenna window is cured at 100-300 DEG C for 12-24 h, so that the cured antenna window is obtained. The silicon-boron-nitrogen precursor is polysilazaborane, and the weight average molecular weight of the polysilazaborane is 7500-8500 g / mol.
[0013] 6. Cracking The antenna window is removed from the mold to obtain a pre-shaped antenna window, the pre-shaped antenna window is transferred to an ammonia furnace in an NH3 atmosphere, and cracked at 600-900 DEG C for 8-12 h, so that the cracked antenna window is obtained.
[0014] 7. Rough machining The cracked antenna window is repeatedly subjected to the steps 3-6 for 5-6 times, so that the antenna window is rough machined to remove a surface dense layer, and a rough machined antenna window blank material is obtained.
[0015] 8. Fine machining The rough machined antenna window blank material is repeatedly subjected to the steps 2-4 for 5-6 times, so that the blank material is fine machined to remove the surface dense layer again, and a fine machined antenna window blank material is obtained.
[0016] 9. Finished product The fine machined antenna window blank material is repeatedly subjected to the steps 2-4 for 5-6 times, so that a mixed nitride composite material special-shaped antenna window is obtained.
[0017] Compared with the prior art, the application has the following beneficial effects: 1. Compared with a single-component nitride fiber preform, a mixed preform of boron nitride and silicon nitride fibers can take into account the performance advantages of both, has excellent high-temperature resistance and ablation resistance of BN, and good mechanical properties of Si3N4, so that the comprehensive performance of the composite material is further improved. In the pretreatment step, the antenna window preform is impregnated with a pretreatment solution. The silicon tetrachloride in the pretreatment solution is hydrolyzed to generate silicon dioxide, and the trimethyl borate is hydrolyzed to generate B2O3, which can form a SiO2-B2O3 eutectic phase to fill the gaps between particles. Combined with supercritical carbon dioxide treatment, it can penetrate into the fiber, improve the uniformity of pore filling, and improve mechanical properties and stability. The antenna window fabricated by contour weaving and contour tooling pre-forming composite preparation changes the traditional antenna window forming method of machining flat raw materials in the middle to carve out the antenna window shape. This greatly reduces raw material consumption, and the internal fiber continuity and orientation consistency of the contour antenna window blank are preserved after processing. Unlike the traditional method of machining complex shapes with composite flat plates, which cuts off a large number of continuous fiber skeletons inside the composite material blank, making the load-bearing performance of complex irregular structural parts with many weak points even worse, the contour weaving preparation, contour tooling impregnation composite, and contour positioning machining can achieve complex antenna window shapes while fully ensuring the mechanical properties of the material. 2. The hybrid nitride composite material irregular antenna window prepared by the method of the present invention has a tensile strength of 47.8-56.4 MPa and a compressive strength of 68.5-78.2 MPa; 3. The hybrid nitride composite material irregular antenna window prepared by the method of this invention has a dielectric loss of 3.6-4.1×10⁻⁶ at 15-17 GHz. -3 ; 4. The hybrid nitride composite material irregular antenna window prepared by the method of this invention exhibits a linear ablation rate of 1.8-2.3 × 10⁻⁶ after 400 s ablation in an oxyacetylene environment at 2500°C. -4 mm / s; 5. The hybrid nitride composite material irregular antenna window prepared by the method of the present invention has a tensile strength of 44.2-53.1 MPa after standing at 1400℃ for 240 h, and a compressive strength of 62.4-73.3 MPa after 25 cycles of thermal cycling at 1800-22℃. Attached Figure Description
[0018] Figure 1-1 , Figure 1-2 Drawings of prefabricated antenna window components; Figure 2-1 , Figure 2-2 , Figure 2-3 , Figure 2-4 To create a contour-following design for tooling. Detailed Implementation
[0019] To provide a clearer understanding of the technical features, objectives, and effects of the present invention, specific embodiments of the present invention are now described.
[0020] Example 1 1. Mixed programming Boron nitride fibers and silicon nitride fibers are blended into a contoured antenna window preform. The preform is in a 3D form, and the volume ratio of silicon nitride fibers to boron nitride fibers is 3:1.5.
[0021] 2. Washing The antenna window preform was placed in the mixture and ultrasonically vibrated for 2.3 hours. The mixture completely submerged the antenna window preform. The ultrasonic frequency was 45 kHz and the ultrasonic power was 110 W. Then it was left to stand for 6 days. After standing, it was transferred to an oven to dry. The oven temperature was 120℃ and the drying time was 24 hours to obtain the washed antenna window preform. In the mixture, the volume ratio of anhydrous ethanol to acetone is 1:1.5.
[0022] 3. Pre-processing Mix 10g silicon tetrachloride with 35g anhydrous ethanol, stir for 35min, then add 0.08g Triton X-100 and 0.14g trimethyl borate, stir evenly to obtain the pretreatment solution; The washed antenna window preform was immersed in a pretreatment solution in a supercritical reactor. The pretreatment solution completely submerged the washed antenna window preform. Then, carbon dioxide was introduced at a flow rate of 1.6 L / min, the temperature was increased to 42 °C, the pressure was 12 MPa, and the mixture was stirred at 230 rpm for 1.5 h. Then, the pressure was reduced to atmospheric pressure at a rate of 0.4 MPa / min. After removal, the preform was placed in a sealed container filled with nitrogen atmosphere and allowed to stand for 1.2 h. Then, it was placed in an environment with room temperature and 83% humidity and allowed to stand for 20 h. After drying, the temperature was increased to 590 °C at a rate of 3.5 °C / min under air atmosphere and held for 1.8 h. Then, the temperature was increased to 910 °C at a rate of 5.0 °C / min and held for 2.7 h. The preform was then cooled to room temperature with the furnace to obtain the initial antenna window.
[0023] 4. Vapor deposition The initial antenna window was suspended in the reaction chamber of a chemical vapor deposition furnace, and NH3, BCl3, and H2 were introduced as reaction gases at flow rates of 3 L / min, 2 L / min, and 4 L / min, respectively. The deposition temperature was 900℃ and the deposition time was 8 h, resulting in a prefabricated antenna window containing the interface.
[0024] 5. Impregnation and curing A contour-following tooling was used to clamp the prefabricated antenna window containing the interface to obtain the clamped antenna window. The clamped antenna window was then transferred to a vacuum mold, evacuated to -0.1 MPa, and left to stand for 2 hours. The silicon boron nitrogen precursor was then siphoned in, and the silicon boron nitrogen precursor completely immersed the clamped antenna window for 4 hours. Then, it was transferred to a high-pressure reactor, and the pressure was controlled at 8 MPa. The mixture was cured at 300°C for 15 hours to obtain the cured antenna window. The silicon-boron-nitrogen precursor is a polyborosilicate, and the weight-average molecular weight of the polyborosilicate is 8500 g / mol.
[0025] 6. Pyrolysis The pre-shaped antenna window is obtained by removing the mold of the solidified antenna window. The pre-shaped antenna window is then transferred to an ammonia furnace under an NH3 atmosphere and pyrolyzed at 900℃ for 8 hours to obtain the pyrolyzed antenna window.
[0026] 7. Rough machining Repeat steps 5-6 six times after the antenna window is pyrolyzed to remove the dense layer on the surface, thus obtaining the rough-machined antenna window blank material.
[0027] 8. Finishing Repeat steps 5-6 four times for the rough-machined antenna window blank material, then perform fine machining on the blank material to remove the dense surface layer again, thus obtaining the fine-machined antenna window blank material.
[0028] 9. Finished product Repeat steps 5-6 four times on the finely machined antenna window blank material to obtain a hybrid nitride composite material irregular antenna window.
[0029] Example 2 1. Mixed programming Boron nitride fibers and silicon nitride fibers are blended into a contoured antenna window preform. The preform is in a 3D form, and the volume ratio of silicon nitride fibers to boron nitride fibers is 3:1.
[0030] 2. Washing The antenna window preform was placed in the mixture and ultrasonically vibrated for 2.0 hours. The mixture completely submerged the antenna window preform. The ultrasonic frequency was 40 kHz and the ultrasonic power was 100 W. Then it was left to stand for 5 days. After standing, it was transferred to an oven to dry. The oven temperature was 100℃ and the drying time was 16 hours to obtain the washed antenna window preform. In the mixture, the volume ratio of anhydrous ethanol to acetone is 1:1.
[0031] 3. Pre-processing Mix 10g silicon tetrachloride with 33g anhydrous ethanol, stir for 30min, then add 0.06g Triton X-100 and 0.12g trimethyl borate, stir evenly to obtain the pretreatment solution; The washed antenna window preform was immersed in a pretreatment solution in a supercritical reactor. The pretreatment solution completely submerged the washed antenna window preform. Then, carbon dioxide was introduced at a flow rate of 1.5 L / min, the temperature was increased to 40 °C, the pressure was 10 MPa, and the mixture was stirred at 220 rpm for 2.0 h. Then, the pressure was reduced to atmospheric pressure at a rate of 0.3 MPa / min. After removal, the preform was placed in a sealed container filled with nitrogen atmosphere and allowed to stand for 1.0 h. Then, it was placed in an environment with room temperature and 80% humidity and allowed to stand for 22 h. After drying, the temperature was increased to 580 °C at a rate of 3.0 °C / min under air atmosphere and held for 2.0 h. Then, the temperature was increased to 900 °C at a rate of 4.5 °C / min and held for 3.0 h. The preform was then cooled to room temperature with the furnace to obtain the initial antenna window.
[0032] 4. Vapor deposition The initial antenna window was suspended in the reaction chamber of a chemical vapor deposition furnace, and NH3, BCl3, and H2 were introduced as reaction gases at flow rates of 1.5 L / min, 0.8 L / min, and 2 L / min, respectively. The deposition temperature was 750℃ and the deposition time was 7 h, resulting in a prefabricated body containing the interface antenna window.
[0033] 5. Impregnation and curing A contour-following tooling was used to clamp the prefabricated antenna window containing the interface to obtain the clamped antenna window. The clamped antenna window was then transferred to a vacuum mold, evacuated to -0.1 MPa, and left to stand for 1.5 hours. The silicon boron nitrogen precursor was then siphoned in, and the silicon boron nitrogen precursor completely immersed the clamped antenna window for 3 hours. Then, it was transferred to a high-pressure reactor, and the pressure was controlled at 7 MPa. The mixture was cured at 200°C for 20 hours to obtain the cured antenna window. The silicon-boron-nitrogen precursor is a polyborosilicate, and the weight-average molecular weight of the polyborosilicate is 8000 g / mol.
[0034] 6. Pyrolysis The pre-shaped antenna window is obtained by removing the mold of the solidified antenna window. The pre-shaped antenna window is then transferred to an ammonia furnace under an NH3 atmosphere and pyrolyzed at 800℃ for 10 hours to obtain the pyrolyzed antenna window.
[0035] 7. Rough machining Repeat steps 5-6 four times after the antenna window has been split, and perform rough machining on the antenna window to remove the dense layer on the surface, so as to obtain the rough-machined antenna window blank material.
[0036] 8. Finishing Repeat steps 5-6 three times for the rough-machined antenna window blank material, then perform fine machining on the blank material to remove the dense surface layer again, thus obtaining the fine-machined antenna window blank material.
[0037] 9. Finished product Repeat steps 5-6 three times on the finely machined antenna window blank material to obtain a hybrid nitride composite material irregular antenna window.
[0038] Example 3 1. Mixed programming Boron nitride fibers and silicon nitride fibers are blended into a contoured antenna window preform. The preform is in a 2.5-dimensional form, and the volume ratio of silicon nitride fibers to boron nitride fibers is 3:0.8.
[0039] 2. Washing The antenna window preform was placed in the mixture and ultrasonically vibrated for 1.8 hours. The mixture completely submerged the antenna window preform. The ultrasonic frequency was 35 kHz and the ultrasonic power was 90 W. Then it was left to stand for 4 days. After standing, it was transferred to an oven to dry. The oven temperature was 80 ℃ and the drying time was 12 hours to obtain the washed antenna window preform. In the mixture, the volume ratio of anhydrous ethanol to acetone is 1:1.2.
[0040] 3. Pre-processing Mix 10g silicon tetrachloride with 30g anhydrous ethanol, stir for 27min, then add 0.05g Triton X-100 and 0.10g trimethyl borate, stir evenly to obtain the pretreatment solution; The washed antenna window preform was immersed in a pretreatment solution in a supercritical reactor. The pretreatment solution completely submerged the washed antenna window preform. Then, carbon dioxide was introduced at a flow rate of 1.4 L / min, the temperature was increased to 38 °C, the pressure was 9 MPa, and the mixture was stirred at 200 rpm for 2.5 h. Then, the pressure was reduced to atmospheric pressure at a rate of 0.2 MPa / min. After removal, the preform was placed in a sealed container filled with nitrogen atmosphere and allowed to stand for 0.8 h. Then, it was placed in an environment with room temperature and 78% humidity and allowed to stand for 24 h. After drying, the temperature was increased to 570 °C at a rate of 2.0 °C / min under air atmosphere and held for 2.5 h. Then, the temperature was increased to 880 °C at a rate of 4.0 °C / min and held for 3.2 h. The preform was then cooled to room temperature with the furnace to obtain the initial antenna window.
[0041] 4. Vapor deposition The initial antenna window was suspended in the reaction chamber of a chemical vapor deposition furnace, and NH3, BCl3, and H2 were introduced as reaction gases at flow rates of 0.5 L / min, 1.5 L / min, and 1 L / min, respectively. The deposition temperature was 600℃ and the deposition time was 5 h, resulting in a prefabricated body containing the interface antenna window.
[0042] 5. Impregnation and curing A contour-following tooling was used to clamp the prefabricated antenna window containing the interface to obtain the clamped antenna window. The clamped antenna window was then transferred to a vacuum mold, evacuated to -0.08 MPa, and left to stand for 1 hour. The silicon boron nitrogen precursor was then siphoned in, and the silicon boron nitrogen precursor completely immersed the clamped antenna window for 2 hours. Then, it was transferred to a high-pressure reactor, and the pressure was controlled at 5 MPa. The mixture was cured at 100°C for 24 hours to obtain the cured antenna window. The silicon-boron-nitrogen precursor is a polyborosilicate, and the weight-average molecular weight of the polyborosilicate is 7500 g / mol.
[0043] 6. Pyrolysis The pre-shaped antenna window is obtained by removing the mold of the solidified antenna window. The pre-shaped antenna window is then transferred to an ammonia furnace under an NH3 atmosphere and pyrolyzed at 600℃ for 12 hours to obtain the pyrolyzed antenna window.
[0044] 7. Rough machining Repeat steps 5-6 three times after the antenna window has been split, and perform rough machining on the antenna window to remove the dense layer on the surface, so as to obtain the rough-machined antenna window blank material.
[0045] 8. Finishing Repeat steps 5-6 twice for the rough-machined antenna window blank material, then perform fine machining on the blank material to remove the dense surface layer again, thus obtaining the fine-machined antenna window blank material.
[0046] 9. Finished product Repeat steps 5-6 twice on the finely machined antenna window blank material to obtain a hybrid nitride composite material irregular antenna window.
[0047] The contoured antenna window prefabricated component described in the embodiment, such as Figure 1-1 , Figure 1-2 As shown, specifically, the bottom is for positioning, the top of the cap is the external surface that receives force and heat, and the inner cavity houses the antenna; The contour-following design tooling described in the embodiments, such as Figure 2-1 , Figure 2-2 , Figure 2-3 , Figure 2-4 As shown, specifically, the contouring tooling mold consists of an inner mold, an outer mold, a gasket, and bolts. The inner mold has eight screw holes evenly distributed around its perimeter, and four screw holes at the bottom of the four ridges at the center protrusion. The eight screws pass through the screw holes around the perimeter, and nuts are screwed onto the screws. When the gasket is used to fit the preform containing the interface antenna window onto the inner mold, the flipped position is exactly in horizontal contact with the gasket platform. After the preform containing the interface antenna window is fitted onto the inner mold, the outer mold is then fitted onto the preform containing the interface antenna window through the studs. Finally, nuts are screwed onto the studs. The clamping thickness of the preform containing the interface antenna window is indirectly controlled by adjusting the height of the nuts.
[0048] In the demolding process, the substrate material filling the gap between the bottom of the inner membrane and the gasket, as well as the inner cavity of the inner mold, is first removed. At this point, the bonding force between the inner membrane and the preform containing the interface antenna window exists only on the inner cavity sidewall of the preform containing the interface antenna window. Then, four screws are inserted slowly and evenly through the four screw holes in the middle position, eventually separating the preform containing the interface antenna window from the inner mold. After the inner membrane is separated, only the bottom gasket and the outer mold fitting part remain. Demolding is then performed sequentially. Compared with direct mold fitting and impregnation curing, the entire demolding process successfully decomposes the bonding force on the inner cavity sidewall and bottom edge, greatly reducing the difficulty of demolding and effectively controlling the risks of deformation and damage to the preform containing the interface antenna window.
[0049] Comparative Example 2-1 The changes made in Example 2 are as follows: 1. Omit the pretreatment step and replace the initial antenna window in the vapor deposition step with a pre-fabricated antenna window after washing; 2. In the impregnation and curing step, polyborosilazane is replaced with silica sol, wherein the mass concentration of the silica sol is 30%; The rest of the operations are exactly the same.
[0050] Performance testing The hybrid nitride composite material irregular antenna windows prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to the following performance tests, as detailed below:
[0051] Among them, the linear ablation rate was measured after ablation for 400 seconds in an oxyacetylene environment at 2500℃. The tensile strength at 1400℃ refers to the tensile strength measured again after being left to stand at 1400℃ for 240 hours. The compressive strength after cold cycling refers to the temperature being increased to 1800℃ at a rate of 30℃ / min, held at that temperature for 1.5h, and then immersed in 22℃ deionized water for 1.5h. This operation constitutes one cycle, and after 25 consecutive cycles, the compressive strength is tested again.
[0052] Unless otherwise stated, all percentages used in this invention are mass percentages.
[0053] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a non-circular antenna window made of hybrid nitride composite material, characterized in that, It includes mixing, washing, pretreatment, vapor deposition, impregnation and curing, pyrolysis, roughing, finishing and finished product steps; The pretreatment step is as follows: silicon tetrachloride is mixed with anhydrous ethanol and stirred for 27-35 min. Then, Triton X-100 and trimethyl borate are added and stirred evenly to obtain a pretreatment solution. The washed antenna window preform is immersed in the pretreatment solution in a supercritical reactor, carbon dioxide is introduced, the temperature is raised to 38-42℃, the pressure is 9-12 MPa, and the mixture is stirred for 1.5-2.5 h. After being removed, it is allowed to stand and dry. Under an air atmosphere, it is kept at 570-590℃ for 1.8-2.5 h and at 880-910℃ for 2.7-3.2 h to obtain the initial antenna window.
2. The method for preparing a hybrid nitride composite material irregular antenna window according to claim 1, characterized in that, The hybridization step involves hybridizing boron nitride fibers and silicon nitride fibers into a contoured antenna window preform. The preform is either 2.5-dimensional or 3-dimensional, and the volume ratio of silicon nitride fibers to boron nitride fibers is 3:0.8-1.
5.
3. The method for preparing a hybrid nitride composite material irregular antenna window according to claim 1, characterized in that, The washing step is as follows: the antenna window preform is placed in the mixed solution and ultrasonically vibrated for 1.8-2.3 hours, the mixed solution completely submerges the antenna window preform, the ultrasonic frequency is 35-45kHz, the ultrasonic power is 90-110W, and then it is left to stand for 4-6 days. After standing, it is transferred to an oven to dry at a temperature of 80-120℃ for 8-24 hours to obtain the washed antenna window preform. In the mixture, the volume ratio of anhydrous ethanol to acetone is 1:1-1.
5.
4. The method for preparing a hybrid nitride composite material irregular antenna window according to claim 1, characterized in that, In the pretreatment solution, the mass ratio of silicon tetrachloride, anhydrous ethanol, Triton X-100 and trimethyl borate is 10:30-35:0.05-0.08:0.10-0.
14.
5. The method for preparing a hybrid nitride composite material irregular antenna window according to claim 1, characterized in that, The vapor deposition step involves suspending the initial antenna window in the reaction chamber of a chemical vapor deposition furnace, introducing NH3, BCl3, and H2 as reaction gases at flow rates of 0.5-3 L / min, 0.1-2 L / min, and 1-4 L / min, respectively, at a deposition temperature of 600-900℃, and for a deposition time of 5-8 hours, to obtain a prefabricated antenna window containing the interface.
6. The method for preparing a hybrid nitride composite material irregular antenna window according to claim 1, characterized in that, The impregnation and curing step is as follows: after clamping, the antenna window is transferred to a vacuum mold, vacuumed to -0.08 to -0.1 MPa, left to stand for 1-2 hours, the silicon boron nitrogen precursor is siphoned in, the silicon boron nitrogen precursor completely immerses the clamped antenna window, impregnates for 2-4 hours, and then transferred to a high-pressure reactor, the pressure is controlled at 5-8 MPa, and cured at 100-300℃ for 12-24 hours to obtain the cured antenna window; The silicon-boron-nitrogen precursor is a polyborosilicate, and the weight-average molecular weight of the polyborosilicate is 7500-8500 g / mol.
7. The method for preparing a hybrid nitride composite material irregular antenna window according to claim 1, characterized in that, The pyrolysis step involves removing the molded antenna window to obtain a pre-shaped antenna window, transferring the pre-shaped antenna window to an ammonia furnace under an NH3 atmosphere, and pyrolyzing it at 600-900℃ for 8-12 hours to obtain the pyrolyzed antenna window.
8. The method for preparing a hybrid nitride composite material irregular antenna window according to claim 1, characterized in that, The roughing, finishing, and final processing steps all involve repeated impregnation, curing, and pyrolysis steps to obtain a hybrid nitride composite material irregular antenna window.
